Georgia : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper reviews the financial sector development in Georgia in recent years, and investigates why it has lagged behind economic development, as well as developments in more advanced transition economies. The paper briefly reviews recent financial sector development in Georgia, comparing it with developments in its neighboring countries in the Caucasus, the seven poorest countries in the Commonwealth of Independent States (CIS-7), the Baltics, and central and eastern Europe. The paper also analyzes possible factors constraining financial intermediation in Georgia and in some of the CIS countries more generally.